Effect of shock wave on optical properties of Propyl p-hydroxybenzoate single crystal: A self-defocusing third order nonlinear optical material. (August 2022) - Nayak, Debabrata; Vijayan, N.; Kumari, Manju; Vashishtha, Pargam; Saini, Saurabh K.; Gangwar, Amit Kumar; Gupta, Govind; Pant, R.P.
Abstract: This work focuses on the effect of shock wave on optical properties of propyl p-hydroxybenzoate single crystal. An optically transparent single crystal was grown by adopting slow evaporation solution growth technique (SEST). Its structure was confirmed by powder X-ray diffraction using Reitveld refinement. The Hirshfeld surface morphology and the intermolecular interaction of titled compound was scrutinized using crystal explorer. Three shock waves generated at constant air compressor pressure of 0.78 Mpa with calculated Mach number 1.7 were allowed to interact with the grown crystal. The UV–vis spectroscopy analysis on shock wave treated sample shows an increase in transmittance for 1st and 2nd shock and a reduction of transmittance for the 3rd shock wave. The defects induced after each shockwave – sample interaction was investigated by photoluminescence spectroscopy and surface morphology studies in detail. The third order nonlinear properties like self – defocusing and reverse saturation absorption of grown crystal were studied using a femto-second Ti-sapphire laser source. The nonlinear absorption coefficient, refractive index were calculated to be 4.04 ˟ 10 −10  cm/W and −8.47 ˟ 10 −15  cm 2 /W using open and closed aperture Z-scan measurement respectively. Graphical abstract: Image 1 Highlights: A shock wave of Mach Number 1.7 was generated with a cost-effective shock wave table top setup. The increment in transmittance of grown Propyl p-hydroxybenzoate crystal was observed for 1st and 2nd shock whereas reduction for 3rd wave. The presence of donor – accepter system and inter molecular interaction was identified with pictorial representation by Hirshfeld analysis. A negative nonlinear refractive index with peak to valley relation in Z-scan shows self-defocusing nature of the crystal.